Karakteristik Pasien Hipertensi di Puskesmas Tabaringan Makassar - Tenri Risna Abdi (Indonesian Journal of Health, 2021)
Hypertension is a condition in which systolic blood pressure (TDS) ≥ 140 mmHg or diastolic blood pressure (TDD) ≥ 90 mmHg that measured by health personnel at least two times. The research objective is to describe the characteristics of hypertensive patients at Tabaringan Health Center. The characteristics referred to gender,age, BMI, and hypertension degree. This research used a descriptive research method by using an observational approach to describe the characteristics of hypertensive patients. The results showed that the total number of male patients with hypertension was 34 (44.7%) and female patients were 42 (55.3%). It found that the number of patients with an age interval of 26 - 45 years was 10 (13.2%) and the number of elderly patients with an age interval> 45 years was 66 (85.8%). The number of hypertensive patients with normal BMI was 16 people (21.1%), overweight was 27 people (35.5%), obesity I was 29 people (38.2%), and obesity II was 4 people (5,2%). It can be seen that the number of patients with a normal degree of hypertension (after routine treatment) was 7 people (9.2%), 22 people with pre-hypertension (28.9%), 39 people with grade I hypertension (51, 3%) and patients with grade II hypertension were 8 people (10.6%). The conclusion is that the gender of hypertensive patients, the number of female patients is more prevalent than male patients, the age of hypertension patients is> 45 years or is included in the elderly category, BMI in patients with overweight nutritional status is much more prevalent than others, and the degree of hypertension in patients was higher in grade 1 hypertension.